Umbilical Cord Cell Therapy Improves Spatial Memory in Aging Rats - Lehmann, Marianne (2019)
There is a growing interest in the potential of adult stem cells for implementing regenerative medicine in the brain. We assessed the effect of intracerebroventricular (icv) administration of human umbilical cord perivascular cells (HUCPVCs) on spatial memory of senile (27 mo) female rats, using intact senile counterparts as controls. Approximately one third of the animals were injected in the lateral ventricles with a suspension containing 4.8 X 105 HUCPVC in 8 μl per side. The other third received 4.8 X 105 transgenic HUCPVC overexpressing Insulin-like growth factor-1 (IGF-1) and the last third of the rats received no treatment. Spatial memory performance was evaluated using a modified version of the Barnes maze test. In order to evaluate learning ability as well as spatial memory retention, we assessed the time spent (permanence) by animals in goal sector 1 (GS1) and 3 (GS3) when the escape box was removed. Fluorescence microscopy revealed the prescence of Dil-labeled HUCPVC in coronal sections of treated brains. The HUCPVC were located in close contact with the ependymal cells with only a few labeled cells migrating into the brain parenchyma. After treatment with naive or IGF-1 transgenic HUCPVC, permanence in GS1 and GS3 increased significantly whereas there were no changes in the intact animals. We conclude that HUCPVC injected icv are effective to improve some components of spatial memory in senile rats. The ready accessibility of HUCPVC constitutes a significant incentive to continue the exploration of their therapeutic potential on neurodegenerative diseases.